Improved Illumination Model of LED Street Light at Rajamangala University of Technology Lanna, Chiang Rai. - พ้นภัย พงศกร; สืบสาร พงษ์ชัย; พรมมี วิฑูรย์ (RMUTL Engineering Journal, 2017)
This research builds a virtual illuminance model of street lights which considers the difference of luminance and illuminance between big-lens and small-lens light emitting diodes (LED) street lights. The location of the study was a street in Rajamangala University of Technology, Chiang Rai campus, where LED Street lights with big lens 70 watt were chosen to replace high intensity discharge (HID) 125 watt lights to save energy, with the exception of some areas which do not have enough light. As a result, LED Street light with small lens are used to improve the light performance of street light. A street lighting model is designed in DIALux program to improve the light performance indices, including illuminance, luminance, and compliance to Thai highway light standards. There are four types of street including Direct road with traffic island, Curve road without traffic island, three ways of a crossroad and four ways of a crossroad. For experimental results, LED Street lights with small lens give a better overall light performance than LED Street light with big lens on the street of Rajamangala University of Technology Lanna, Chiang Rai.